Selenium nanoparticles in aquaculture: Unique advantages in the production of Se-enriched grass carp (Ctenopharyngodon idella) - Chao Zhu; Zifang Wu; Qimin Liu; Xiaolin Wang; Lijuan Zheng; Shuyang He; Fangxia Yang; Hong Ji; Wuzi Dong (Animal Nutrition, 2024)
The production of selenium-enriched fish can contribute to alleviating selenium deficiency in human diets. However, it is still unclear which selenium source, as an additive, can efficiently and cost-effectively produce high-quality selenium-enriched fish. This study evaluated the effects of selenium nanoparticles (SeNP), selenite, and selenomethionine (SeMet) on the growth, antioxidant capacity, selenium content, selenium speciation, and meat quality of grass carp. Ten diets were prepared, including a basal diet (BD) and three concentrations (0.1, 0.3, and 0.9 mg/kg) of SeNP, selenite, and SeMet. A total of 600 fish (250.79 ± 1.57 g) were randomly assigned to 30 tanks (3 tanks/group). Fish were fed the experimental diet three times daily for 60 d. In this study, SeNP most significantly promoted the growth and antioxidant capacity of grass carp, with 0.3 mg/kg SeNP identified as the optimal additive concentration. Additionally, SeNP demonstrated equally excellent bioavailability as SeMet and significantly increased the content of SeMet in grass carp (Ctenopharyngodon idella) muscle. Furthermore, compared to SeMet and selenite, dietary SeNP could more significantly enhance the content of selenocysteine (SeCys2) and methylselenocysteine (MeSeCys) in grass carp muscle tissue. In addition, we have demonstrated that SeCys2 and MeSeCys promote apoptosis of cancer cells (HeLa) through the mitochondrial apoptotic pathway (involving Bax and Bcl-2). Furthermore, as an additive, 0.3 mg/kg SeNP significantly improved the flesh quality of grass carp by reducing crude fat and heavy metal content, as well as increasing the levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and the ratio of n-3/n-6 polyunsaturated fatty acid (PUFA). In summary, SeNP is the most suitable additive for producing selenium-enriched fish.